Perancangan User Interface dan User Experience Aplikasi Pemandu Wisata Kebun Binatang Menggunakan Metode User Centered Design - Muhamad Ifan Nuriyana; Eko Setia Budi (STMIK Budi Darma, 2023)
The development of technology in recent years has transformed the way humans interact with computers and has extended to various aspects of life, including the tourism sector, contributing to the distribution of more interactive information about tourist attractions, particularly through mobile applications. One of the emerging applications is the zoo tour guide application. Based on questionnaire results and processed using the System Usability Scale (SUS) method with an average score of 99.5 and a rating of